Excellent outcomes of transformed lymphomas in the rituximab era without autologous stem cell transplantation: an Australian single‐centre experience. Issue 11 (24th October 2021) - Tedjaseputra, Aditya; Gilbertson, Michael; Low, Michael; Fedele, Pasquale L.; Kumar, Beena; Simpson, Ian; Grigoriadis, George; Shortt, Jake; Opat, Stephen; Gregory, Gareth P.
Abstract: Background: Histologic transformation (HT) is an important event with adverse prognosis in the natural history of indolent lymphomas. There are minimal data on HT in the Australian setting. Aims: To characterise patients with biopsy‐proven HT and their outcomes identified at a tertiary Australian Hospital. Methods: All patients with biopsy‐proven HT during a 15‐year period (2002–2017) were included. Clinico‐pathological data were systematically collected from review of patient records. Survival estimates were assessed using the Kaplan–Meier method and compared using the log‐rank test. Associations between variables and clinical outcomes were evaluated using Cox's proportional hazards model. Results: A cohort of 45 patients was identified with a median age of 66 years and the majority (59%) having high‐risk disease (Revised‐International Prognostic Index score ≥3). R‐CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) induction was used in 69%, with an overall response rate of 82% (complete response (CR), 75%). Sixty‐one percent of these induction responders received consolidation, with autologous stem cell transplant (ASCT) performed in only 17% and rituximab maintenance given to 31%. With a median follow up of 47 months (range: 4–136), the 5‐year overall survival (OS) was 69% (95% CI: 52%, 81%). Chemotherapy‐naivety at HT was associated with a superior rate of CR (84% vs 54%, P = 0.057) and 5‐year OS (82% vs 46%, P = 0.012). Rituximab maintenance was associated with a durable progression‐free survival in induction responders. Conclusions: Excellent OS was observed in this modern cohort of patients treated with rituximab‐containing induction and low rate of consolidation by ASCT, particularly in those who were chemotherapy‐naïve at HT.